2012
DOI: 10.1593/neo.12724
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Basophils as a Major Source of Hepatocyte Growth Factor in Chronic Myeloid Leukemia: A Novel Mechanism of BCR-ABL1-Independent Disease Progression

Abstract: Chronic myeloid leukemia (CML) is a hematopoietic neoplasm characterized by the Philadelphia chromosome and the related BCR-ABL1 oncoprotein. Acceleration of CML is usually accompanied by basophilia. Several proangiogenic molecules have been implicated in disease acceleration, including the hepatocyte growth factor (HGF). However, little is known so far about the cellular distribution and function of HGF in CML. We here report that HGF is expressed abundantly in purified CML basophils and in the basophil-commi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 34 publications
0
57
0
4
Order By: Relevance
“…55, 56, 57, 58 In particular, it has been described that patients with CML exhibit elevated HGF levels in their PB and BM and that expression of HGF in the BM correlates with the microvessel density in BM sections 55, 56, 57, 58. Moreover, increased PB levels of HGF correlate with the prognosis in CML 57, 58. Other studies have shown that HGF is specifically synthesized by CML basophils and that basophil‐derived HGF promotes migration and growth of endothelial cells through a specific receptor 58.…”
Section: Basophils As Unique Source Of Microenvironment‐remodelling Smentioning
confidence: 99%
See 3 more Smart Citations
“…55, 56, 57, 58 In particular, it has been described that patients with CML exhibit elevated HGF levels in their PB and BM and that expression of HGF in the BM correlates with the microvessel density in BM sections 55, 56, 57, 58. Moreover, increased PB levels of HGF correlate with the prognosis in CML 57, 58. Other studies have shown that HGF is specifically synthesized by CML basophils and that basophil‐derived HGF promotes migration and growth of endothelial cells through a specific receptor 58.…”
Section: Basophils As Unique Source Of Microenvironment‐remodelling Smentioning
confidence: 99%
“…However, not all angiogenic and fibrogenic cytokines are produced in CML cells in a BCR‐ABL1‐dependent manner. For example, HGF is produced in CML basophils independent of BCR‐ABL1 58. In fact, the biochemical basis underlying expression and release of HGF in basophils in CML remains at present unknown.…”
Section: Basophils As Unique Source Of Microenvironment‐remodelling Smentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, patients with CML frequently exhibit basophilia in the BM and peripheral blood (PB), which becomes more pronounced in the accelerated phase. 3,4 However, the pathogenic roles of basophil-like leukemia cells during disease progression are poorly understood because of a lack of information on the molecule(s) produced by these cells.…”
Section: Introductionmentioning
confidence: 99%